Synthesis, Characterization, and Crystal Structure Refinement of Lanthanum and Yttrium Substituted Polycrystalline 2M Type Zirconolite Phases: Ca1-xMxZrTi2O7 (M = Y, La and x = 0.2). (21st August 2014) - Bohre, Ashish; Avasthi, Kalpana; Shrivastava, O. P.
Abstract : Solid phases of zirconolite-2M with composition Ca0.8 M0.2 ZrTi2 O7 (M = La, Y) have been synthesized through ceramic route and their structures refined to a satisfactory convergence using Rietveld analysis. Zirconolites crystallize in space group C2/c with Z = 8. The powder diffraction data of Ca0.8 Y0.2 ZrTi2 O7 (CZTY) and Ca0.8 La0.2 ZrTi2 O7 (CZTLa) have been subjected to General Structural Analysis System software to arrive at a satisfactory structure fit with Rp = 0.1128 and Rwp = 0.1805 for CZTY and Rp = 0.1178 and Rwp = 0.1874 for CZTLa, respectively. The unit cell parameters are a = 10.1708 (6) Ǻ, b = 6.2711 (4), and c = 11.2779 (6) Ǻ for CZTY and a = 11.2548 (6) Ǻ, b = 6.2601 (4), and c=11.2606 (7) Ǻ for CZTLa. Calculated interatomic distances and bond angles are in good agreement with their standard values. Particle size along prominent reflecting planes calculated by Scherrer's formula ranges between 67 and 107 nm. The polyhedral (CaO8, ZrO7, and TiO6 /TiO5 ) distortions and valence calculation based on bond strength analysis have been reported. The compositions of the zirconolites were determined using energy dispersive X-ray (EDAX) analysis. Cation site occupancies were determined by applied compositional constraints which were found consistent with the expected zirconolite-2M cation site occupancies.